Pengembangan Media Pembelajaran Berbasis Aplikasi Lectora Inspire untuk Meningkatkan Pemahaman Matematis dalam Penerapan Problem Based Learning - Ribka Sonya Rajagukguk; Prihatin Ningsih Sagala (Departement of Mathematics Education, 2024)
Researchers created a learning medium based on the Lectora Inspire Application based on the findings of a requirements analysis throughout the learning process. The goal of this study is to make this product more legitimate, practical, and useful in boosting students' mathematical comprehension. The ADDIE (Analyze, create, Development, Implementation, and Evaluation) development paradigm was used by researchers to create this study and development. This study included 30 students from class XI Science 1 SMA Negeri 1 Simanindo. According to the research findings, the produced Lectora Inspire Application-based learning media has a high degree of validity, with an average percentage of 87.08% according to material experts and 89.61 according to media experts. Positive reactions from instructors and students were also discovered during small group and large group trials, with an average score of 92% from teachers, 94.6% from small groups, and 90.2% from big groups. This demonstrates that this medium is quite useful in the learning process. Aside from that, the outcomes of applying this interactive learning media demonstrate its efficacy. The completion rate of classical learning was 86.67%, and the efficacy questionnaire received an average percentage of 93.44%. The development in pupils' mathematical comprehension might be classified as modest. Based on the findings of this study, it is possible to conclude that the Lectora Inspire application-based learning media produced satisfied the requirements of being valid, practical, and successful in boosting students' mathematical comprehension.